FORMULATION AND EVALUATION OF DRY POWDER INHALABLE NANOPARTICLES FOR THE TREATMENT OF COVID-19 - VS, SAGAR; K., JANAKIRAMAN; AKHIL; J., JOYSA RUBY (International Journal of Applied Pharmaceutics, 2025)
Objective: This work sought to develop and assess remdesivir (REM) nanoparticles to achieve increased pulmonary administration, prolonged drug release, and enhanced bioavailability through a polymer-based nanoparticulate system. Methods: REM nanoparticles were synthesised utilising Poloxamer 407 and HPMC E3 by a solvent evaporation method. The formulation was analysed for drug content, particle size (PS), surface morphology, and thermal properties. In vitro drug release tests were performed to assess the release profile for 48 h. Kinetic modelling was conducted to ascertain the release mechanism, and stability experiments were executed to evaluate long-term formulation stability. Results: The nanoparticulate system has a PS of 228.3±37.64 to 492.22±174.6 nm and zeta potential (ZP) of-17±5.31 to-27.3±6.76 mV. The F4 nanoparticles exhibited precise drug content and homogenous PS, with Scanning Electron Microscopy (SEM) examination indicating a well-defined surface shape suitable for pulmonary delivery. In vitro release experiments demonstrated a sustained release profile, with 78.96% cumulative release over 48 h. The release mechanism was determined to be non-Fickian diffusion or erosion-controlled. Differential Scanning Calorimetry (DSC) analysis verified the total encapsulation of the medication within the polymer matrix. Stability experiments revealed no substantial alterations in PS, polydispersity index (PDI), ZP throughout the storage period. Conclusion: The optimised REM nanoparticle formulation (F4) demonstrated favourable attributes for regulated pulmonary drug administration, featuring prolonged release and stable physicochemical features. These findings indicate significant industrial and therapeutic potential; nevertheless, additional clinical assessment is required to verify in vivo efficacy and safety.